Respons Pertumbuhan Bibit Setek Tanaman Buah Naga Merah (Hylocereus costaricencis (Web) Britton & Ross) Terhadap Pemberian Auksin Alami dengan Berbagai Tingkat Konsentrasi - Muhammad Rivai Sitorus; T. Irmansyah; Ferry Ezra Sitepu (Jurnal Agroekoteknologi, 2015)
One way to increase the production of dragon fruit is the provide of quality seeds. Used of coconut water, cow urine, and goat urine which is contains the hormone auxin that could potentially increase the growth of seedlings. This research was conducted in Agriculture Faculty University of Sumatra Utara with a height ± 25 m above sea level, which is held in May until July 2015. The research used randomized block design with 2 factors, namely, the type comprised a natural auxin of coconut water, cow urine, goat urine and concentration consisting of 0,25,50,75 and 100% were repeated three times. continiued analyzed used analysis of variance followed by Duncan's Multiple Range Test (DMRT) at 5%. The result showed that the type of natural auxin has significantly effect against age emerged shoots and shoots height 30 DAP. The concentration of natural auxin significantly effect against emerged shoots, shoot height 30, 45 DAP, and dry weight of shoots. Interaction between types of natural auxin and concentration has significantly effect against age emerged shoots, and height shoots 30 DAP.Key word : type of natural auxin, concentration of natural auxin. cut dragon fruit